Reflections on equity and its applicability to the nursing work process - Nair Chase da Silva; Hadelândia Milon Oliveira (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to reflect on the principle of equity from the perspective of social justice and its applicability in the dimensions of the nursing work process. Methods: theoretical essay on the challenges for the practice with equity in the dimensions of the Nursing work process: teaching, care, research, political participation and administration. Results: the principle of equity should: in education be transversal in the training of future professionals; in assistance to occur without privilege or discrimination, treating the unequal unequally and the equals equally; in research be the target in the creation of new knowledge; in political participation to count on the contribution of social movements; and in the administration to count on the creation of specific executable policies. Final Considerations: there are still inequalities in access to services by part of the Brazilian population. Nursing should promote in its work process the implementation of equity promotion policies with a view to social justice.